Higher Soluble CD163 in Blood Is Associated With Significant Depression Symptoms in Men With HIV. (1st November 2022) - Anderson, Albert M.; Bhondoekhan, Fiona; Curanovic, Dusica; Connelly, Margery A.; Otvos, James D.; Post, Wendy S.; Michos, Erin D.; Stosor, Valentina; Levine, Andrew; Seaberg, Eric; Weinstein, Andrea M.; Becker, James T.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: People with HIV (PWH) are more likely to experience depression, a highly morbid disease. More evidence is needed to better understand mechanisms of depression in PWH. We evaluated a panel of blood biomarkers in relation to depression symptoms in the Multicenter AIDS Cohort Study (MACS). Setting: Four sites in the United States. Methods: A cross-sectional analysis was performed within the MACS, a prospective study of cisgender men with and without HIV. Depression was assessed with the Center for Epidemiological Studies-Depression Scale, and six blood biomarkers were measured: GlycA, high sensitivity C-reactive protein (CRP), interleukin-6, CCL2, soluble CD14 (sCD14), and soluble CD163 (sCD163). Using univariable and multivariable logistic regression, the biomarkers and other factors were evaluated in relation to significant depression symptoms (SDS) by Center for Epidemiological Studies-Depression score ≥16. Results: 784 men were analyzed; most of whom (63%) were PWH. PWH were more likely to have SDS (32% vs. 21%). In univariable analysis, higher GlycA, CRP, and sCD163 concentrations were associated with SDS. In multivariable analysis, however, only higher sCD163 concentration was associated with SDS (odds ratio = 2.30, 95% CI = 1.11 to 4.76). This relationship was driven by the PWH group (odds ratio = 2.72, 95% CI = 1.12 to 6.58) and remained significant when controlling for antidepressant use. Lack of college education was also associated with SDS. Conclusions: Higher sCD163, a marker of macrophage activation, was significantly associated with significant depression symptoms in the MACS. Further research on this biomarker and macrophage activation in general is warranted to better understand and treat depression in PWH.